PENGARUH PENGGUNAAN MEDIA GAMBAR TERHADAP KEMAMPUAN MENULIS PUISI PADA SISWA KELAS X SMK SWASTA TERUNA PADANGSIDIMPUAN - Dalimunthe, Fatma Hayati; Hasibuan, Nikmah Sari; Lubis, Khatib (Linguistik : Jurnal Bahasa dan Sastra, 2024)
AbstractÂ This research aims to determine the influence of using visual media on students' ability to write poetry in the 10th grade of Teruna Padangsidimpuan Private Vocational School. The method used is quantitative research. The population of the study consists of 10 classes with a total of 285 students, and the sample is taken from the Machining Engineering class, totaling 33 students. Data collection technique involves 10 multiple-choice test questions (variable X) and 5 essay test questions (variable Y). Data analysis is conducted using the Pearson product-moment correlation formula "r." The results of the study show that the highest scores obtained for each variable are 90 and the lowest scores are 70, with average scores of 85.75 for variable X and 84.24 for variable Y. The value obtained from the Pearson product-moment correlation table is 0.419, considering the correlation "r" table with a value of 0.355 at a 5% error level with 33 degrees of freedom. This means that rcomputed=0.419 or rcomputed 0.4190.355, indicating that the students' average level falls into the "Good" category. Therefore, it can be concluded that there is an influence of using visual media on students' ability to write poetry in the 10th grade of Machining Engineering at Teruna Padangsidimpuan Private Vocational School in the academic year 2023-2024.